Rifampicin resistance among patients with Tuberculosis at the Olabisi Onabanjo University Teaching Hospital, Sagamu - Daniel Olusoji James; Bamidele Olufisayo Janet; Sodeinde John Kolawole; Ekundayo Adeola Adebayo; Salako Albert Adekunle (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: Tuberculosis (TB) is a major public health problem in Nigeria. The emergence of multidrug-resistant Tuberculosis poses a threat to global Tuberculosis control and if not effectively addressed, may wipe out the achievements of previous efforts in controlling Tuberculosis. Objectives: To determine the prevalence and factors associated with rifampicin resistance amongpatients receiving care for TB at the OlabisiOnabanjo University Teaching Hospital, Sagamu. Methods: A retrospective study of presumptive Tuberculosis cases managed between January 2013 and December 2016 at the Directly Observed Treatment clinic, OlabisiOnabanjoUniversity Teaching Hospital Sagamu, Ogun State, Nigeria,was done. One sputum sample was obtained from each patient for the Gene Xpert® test to diagnoseTB and to determine rifampicin resistance among patients with confirmed Mycobacterium tuberculosis infection. HIV screening was also carried out on all the patients using HIV Rapid Test kits. The sociodemographic data were retrieved from the presumptive Tuberculosis register. Results: A total of 1572 presumptive TB patients were screened for TB, out of which 187 (11.8%) were confirmed to be infected with Mycobacterium tuberculosis (MTB). A total of 20 (10.7%) of the 187 MTB patients had rifampicin resistance using Gene Xpert® method. Rifampicin resistance rate was significantlyassociated with re-treatment TB category but not with age, sex or HIV status. Conclusion: The study showed rifampicin drug resistance among confirmed TB patients. There is a need to decentralizethe use of Gene Xpert® test for TB to the peripheral facilities and make it a point of care test for presumptive TB patients.